Boron-based stepwise dioxygen activation with 1,4,2,5-diazadiborinine - Wang, Baolin (2019)
Activation of dioxygen (O2) by 1,4,2,5-diazadiborinine 1 is reported. Two boron centers in 1 undergo a formal [4 + 2] cycloaddition with O2 at room temperature affording a bicyclo[2.2.2] molecule 2 featuring a B–O–O–B unit. Treatment of 2 with an additional equivalent of 1 leads to the cleavage of the O–O bond in 2 concomitant with the formation of two B–O bonds to yield 4 involving the extremely rare B4C2N2O2 ten-membered rings. A series of these reactions demonstrate the stepwise scission of the O[double bond, length as m-dash]O π-bond and the O–O σ-bond of O2.